Formulation Designing and Optimization of Loteprednol-loaded spanlastic Nanocarriers for Treatment of Ocular Inflammation (Asian Journal of Pharmaceutics (AJP), 2023)
Objective: The objective of this scientific work was focused on formulation, optimization and evaluation ofloteprednol-loaded spanlastic nanocarriers for effective treatment of ocular inflammation with enhancedtranscorneal drug permeation, prolonged corneal residence time, and sustained drug release profile.Materials and Methods: The spanlastic nanocarriers of loteprednol was prepared by ethanol injection methodusing Span 60 and Tween 80 as vesicular components. A 23 factorial design was employed in the optimization studiesselecting independent variables such as Span 60, Tween 80, and drug content, whereas, the response variables suchas particle size, polydispersity index, zeta potential, entrapment efficiency, and cumulative % drug release. Theoptimized formulation was evaluated for various in vitro and ex vivo parameters. Results and Discussion: Theoptimized formulation of spanlastic nanocarriers of loteprednol was found to have 207.4 nm particle size, 0.41polydispersity index, −0.62 mV zeta potential, and 58.23% entrapment efficiency. The cumulative % drug releasewas 98.45% during 8-h period exhibiting sustained release and Korsmeyer-Peppas model release kinetics. Theex vivo drug permeation study across goat eye cornea exhibited apparent permeability (Papp) of 11.95 cm/min-1and steady-state flux (Jss)of 19.45 mg/cm2 min-1which was >5 times higher than marketed product. The developedformulation maintained its physical characteristics and possessed all desired product quality attributes in theideal range. Conclusion: The developed loteprednol loaded spanlastic nanocarriers demonstrated all the qualityparameters very close to the software predicted values and also exhibited enhanced transcorneal drug permeationwhich would lead to higher ocular drug bioavailability and need of less frequent drug administration in effectivemanagement of ocular inflammation.